Serological tests in the differentiation of staphylococcal and tuberculous bone disease. - Taylor, A G (1975)
The haemagglutination test for antileucocidin is frequently positive in cases of bone tuberculosis in the absence of obvious staphylococcal infection. This test is therefore of little practical use in the differentiation of staphylococcal and tuberculous bone disease, and its use has been discontinued at the Royal National Orthopaedic Hospital. The antigamma haemolysin test in bone tuberculosis appears to give rise to few false positive results. Our observations confirm that the anti-alpha haemolysin and antigamma haemolysin tests used together reveal about 80 percent of cases of staphylococcal bone infection on first presentation or relapse.